(untitled) (Plant Bulletin, 2025)
Camelina sativa has emerged as a promising oilseed crop for biodiesel and ethanol production due to its high yield potential under minimal input conditions, making it suitable for marginal and rainfed lands. In this study, a three-year field evaluation of 50 mutant lines was conducted under sub-tropical low-input conditions to assess morphological variation and oil quality. Significant genetic variability was observed across key agronomic traits such as plant height (48–78 cm), capsule number (338–5627), and seed yield (6–14 g per plant), indicating ample scope for selection. Fatty acid profiling revealed considerable variation in oleic acid (0–26.5%) and palmitoleic acid (0–63.6%), with several lines rich in unsaturated fatty acids, essential for biodiesel quality and oxidative stability. Notably, mutant lines 6783, 4844, 5958, 5989, and 6725 exhibited superior yield performance, while lines such as 6862, 6882, 5296, and 6795 showed desirable oil profiles for biofuel. These findings underline the potential of selected mutant lines to serve as climate-resilient, low-input feedstock for sustainable biodiesel production. This work contributes toward the development of environment-friendly cropping systems and energy diversification strategies aligned with climate adaptation and SDG 7 (Affordable and Clean Energy) and SDG 13 (Climate Action) goals.